Growth, replication and division enable evolution of coacervate protocells. Issue 80 (21st September 2022) - Slootbeek, Annemiek D.; van Haren, Merlijn H. I.; Smokers, Iris B. A.; Spruijt, Evan
Abstract : In this Feature Article, we analyze how a minimal cell cycle of growth, replication of genetic information and division could be realized in coacervate protocells. This would allow such primitive cells to undergo evolution at the origins of life. Abstract : Living and proliferating cells undergo repeated cycles of growth, replication and division, all orchestrated by complex molecular networks. How a minimal cell cycle emerged and helped primitive cells to evolve remains one of the biggest mysteries in modern science, and is an active area of research in chemistry. Protocells are cell-like compartments that recapitulate features of living cells and may be seen as the chemical ancestors of modern life. While compartmentalization is not strictly required for primitive, open-ended evolution of self-replicating systems, it gives such systems a clear identity by setting the boundaries and it can help them overcome three major obstacles of dilution, parasitism and compatibility. Compartmentalization is therefore widely considered to be a central hallmark of primitive life, and various types of protocells are actively investigated, with the ultimate goal of developing a protocell capable of autonomous proliferation by mimicking the well-known cell cycle of growth, replication and division. We and others have found that coacervates are promising protocell candidates in which chemical building blocks required for life are naturally concentrated, and chemical reactions can be selectively enhanced or suppressed. This feature article provides an overview of how growth, replication and division can be realized with coacervates as protocells and what the bottlenecks are. Considerations are given for designing chemical networks in coacervates that can lead to sustained growth, selective replication and controlled division, in a way that they are linked together like in the cell cycle. Ultimately, such a system may undergo evolution by natural selection of certain phenotypes, leading to adaptation and the gain of new functions, and we end with a brief discussion of the opportunities for coacervates to facilitate this.